The Patient’s Narrative Agenda as an assessment tool: the story of Robert, suffering from osteosarcoma - Artioli, Giovanna; Foà, Chiara; Cosentino, Chiara; Taffurelli, Chiara; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. To activate the participation of the person in his/her care path, the literature highlight the impact of the professional’s ability to show a genuine interest in the problems brought by the patient and to recognize him/her as ‘competent’. In these sense the narrative patient’s agenda could be a useful relational tool, because is focused on the perception of patient experiences of his/her illness. Thus this study aims to analyze the usefulness of patient’s narrative agenda during the assessment phase. Method. A semi-structured interview has been adopted to explore the agenda of Robert, 21 years old, suffering from osteosarcoma. A first level analysis identified the four functional areas of the agenda: ideas and beliefs; expectations and desires and context in which he lives and interacts. A second level analysis assessed the main Robert’s problems. Results. The narrative agenda has highlighted many central problems of Robert (e.g. therapeutic adherence, quality of life, mood, body image, existential problems related to experiences, hopes and expectations). Of course these results could be integrated with other tools: qualitative, to understanding difficulties and to formulate hypotheses, and quantitative, to measure the level of severity of problems reported. Discussion and conclusion. The narrative agenda has not only proved to be a valid instrument of assessment, allowing an adequate insight on the patient’s problems, as we exemplified, but it can be also used for monitoring the dynamic situation of the person’s history, lending itself to the re-exploration of its functional areas over time.